Maple computer guide : a self-contained introduction for Advanced engineering mathematics - Kreyszig, Erwin. (John Wiley and Sons, 2001)
Ordinary differential equations (ODE's). Linear algebra, vector calculus. Fourier analysis and partial differential equations. Numerical methods...